TEKNIK PENGGUNAAN MEDIA PEMBELAJARAN AUDIO VISUAL PADA MADRASAH IBTIDAIYAH - Moch. Shohib; Moch Mahsun (Research Institute and Community Engagement of IAIN MADURA, 2021)
The appear disruption era with the rapid technology development gives a positive effect to development of world industry and makes a decline effect of religious character of the next generation Indonesia, it was not exeepted in a small town like in Lumajang that’s the biggest population comes from Madura. The Madurese ethnic believed the leadership of Kiai as central figure in pesantren’s environment in establishment religious character of around environment. This research isa kind of qualitative descriptive, otherwise the date collection technig uses interview, observation and documentation in pesantren’s Darul Ulum or the society who lives around it. Next the data will be analyzed by tree angulation and date reduction to take the conelusion. This research showed that Madurese pesantren’s culture was belived by society can from religious character by reparing and increasing pesantren’s tri dharma (tree obligation) since built pesantren in Indonesia, in order that the education in Indonesia creates the gold generation 2045